Do Large Cabinets Favor Large Governments? Evidence on Institutional Restraints on the Fiscal Commons Problem for Swiss Cantons - Christoph A. Schaltegger; Lars P. Feld (Center for Research in Economics, Management and the Arts (CREMA), 2008)
The fiscal commons problem is one of the most prominent explanations of excessive spending in political economics. The more fragmented a government, the higher its spending. In this paper we investigate to what extent this problem can be mitigated by different fiscal or constitutional insti-tutions. We distinguish between two variants of fragmented governments: cabinet size and coali-tion size. In addition, we analyze whether constitutional rules for executive and legislature as well as formal fiscal restraints shape the size of government and how different rules interact with fragmentation in determining government size. The empirical analysis of the role of fragmented governments for fiscal policy outcomes is based on a panel of 26 Swiss cantons from 1980-1998. The results indicate that the number of ministers in the cabinet is negatively associated with fiscal discipline. Furthermore, fiscal referendums effectively restrict the size of government, while for-mal fiscal restraints more effectively restrict the fiscal commons problem. (This is a thoroughly revised version of Crema WP Nr. 2004-15)
Keywords: E61; E63; H61; 330; Fragmentation; Fiscal Policy; Referendums; Legislative Rules; Formal fiscal restraints